An iron hand upon the people the law against the Potlatch on the Northwest Coast - Cole, Douglas; Chaikin, Ira (Douglas & McIntyre u.a., 1990)
Re-examination of the history of the potlatch, the law and the Indians response to the legislation. Despite being subjected to a paternalism that became increasingly authoritarian, British Columbia's Indians remained significant participants in their own cultural destiny.